Diagnosis Of Breast Lesions- Fine Needle Aspiration Cytology (Fnac) Or Core Needle Biopsy? - Ankita Baghel; CSBR Prasad; M.L. Harendra Kumar (Journal of Clinical and Biomedical Sciences)
Breast lesions are very common among Indians, being the 2nd most common cancer site. Diagnosis of breast lesions is routinely done by triple assessment. FNAC and Core needle biopsy (CNB) being the method of choice for Pathological diagnosis. Objectives: Are to compare sensitivity and specificity of FNAC and CNB in diagnosing breast lesions and to evaluate their diagnostic usefulness and also assessing invasion, tumor grade and ER/PR status. Materials and Methods: Forty two patients, who presented to RL Jalappa hospital with breast lesions, underwent physical examination and both FNAC and CNB were done. Grading and ER/PR status was done for the malignant tumors using standard criteria on the same day using cytology smears and frozen sections. The results were compared with histopathological findings in excised specimens. Result: CNB was found to have higher sensitivity and specificity as compared to FNAC in diagnosing breast lesions. In all malignant cases assessment of invasion by core biopsy correlated well with excised specimens. Conclusion: CNB was able to give histological diagnosis with additional information which will affect the treatment. Keywords: FNAC, Core biopsy, Estrogen receptor, Progesterone receptor